Aplikasi My Angkot - Sofyan Mufti Prasetiyo; Mahardika Paramarta Laia; Dewy Suciati; Nurul Syifa Fauzia Paksi (CV. Multi Kreasi Media, 2023)
Public transportation is a means of transportation for the community to facilitate transportation in everyday life. Public transportation is the main choice because everyone can use it and the fare is relatively cheap to get to their destination. Most people use this facility to travel or to get to their destination. The need to know the fastest angkot route is quite urgent for angkot service users, especially those who are inexperienced. So, it is necessary to have an application regarding public transport routes and can avoid jostling with other passengers. Then the